Penerapan Metode MDLC pada Perancangan Video Profile Sekolah Advent Mision Sagulung - Putri Utami; Hendi Sama (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The Adventist Mission School is a private school located in Batam, Sagulung, to be exact, in the Riau Archipelago. The Adventist Mission School was founded in 2001; the Adventist Mission School has levels from kindergarten to high school. As media grows, schools need informational and promotional materials in more flexible formats such as video profiles. However, the school does not yet have a profile video that can be used for information and promotion so the author will design a profile video for the Adventist missionary school. This activity specifically targets Profile Videos to help schools design information materials for school promotions. The research results from making a video profile at Mission Sagulung Adventist School will produce strategies that can be applied to help schools present and promote schools to all Batman residents.